Renal Transplant Pathology: Demographic Features and Histopathological Analysis of the Causes of Graft Dysfunction - Shaarif Bashir; Mudassar Hussain; Azhar Ali Khan; Usman Hassan; Khawaja Sajid Mushtaq; Maryam Hameed; Usman Ayub Awan (International Journal of Nephrology)
Background. Renal transplant has emerged as a preferred treatment modality in cases of end-stage renal disease; however, a small percentage of cases suffer from graft dysfunction. Aim. To evaluate the renal transplant biopsies and analyze the various causes of graft dysfunction. Materials and Methods. 163 renal transplant biopsies, reported between 2014 and 2019 and who fulfilled the inclusion criteria, were evaluated with respect to demographics, clinical, histological, and immunohistochemical features. Results. Of 163 patients, 26 (16%) were females and 137 (84%) were males with a mean age of 34 ± 7 years. 53 (32.5%) cases were of rejection (ABMR and TCMR), 1 (0.6%) was borderline, 15 were of IFTA, and rest of 94 cases (57.7%) belonged to the others category. SCr (serum creatinine) in cases of rejection was 3.85 ± 0.55 mg/dl. Causes of early graft dysfunction included active ABMR (7.1 ± 4.7 months), acute TCMR (5.5 months), and acute tubular necrosis (after 6 ± 2.2 months of transplant) while the causes of late rejection were CNIT and IFTA (34 ± 4.7 and 35 ± 7.8 months, respectively). Conclusion. Renal graft dysfunction still remains a concerning area for both clinicians and patients. Biopsy remains the gold standard for diagnosing the exact cause of graft dysfunction and in planning further management.